Analysis of Entrepreneurial Interest in Biology Education Students after Attending Plant Structure and Development Course - Rahmadhani Fitri; Lufri Lufri; Heffi Alberida; Yuni Ahda; Ali Amran; Kiki Mulyani (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2024)
One of the objectives of the Biology Education study program is that students have entrepreneurial insights and competencies in the field of biology education that can contribute to self-development and society. Based on the objectives of this study program, it can be concluded that graduates of the study program are not only expected to become teachers but also to become entrepreneurs. Therefore, in the lecture process, it is hoped that each course can be oriented to foster students' entrepreneurial interest and motivation. This study aims to reveal how the entrepreneurial interest of Biology Education students after taking the Plant Structure and Development course. Because of the potential of this course if the right project assignment is developed in fostering the entrepreneurial spirit, this will be able to form graduates who have entrepreneurial competencies. This research is an exploratory descriptive research. The data were analyzed with descriptive statistics and the results of the data analysis were later interpreted in qualitative form. The results showed that 91.37% of students are interested in entrepreneurship and the level of entrepreneurial interest of students has a high category. Based on the results of the study it can be concluded that the entrepreneurial interest of Biology Education students after taking the course of Plant Structure and Development has a high category.